Homeland consciousness and literary evolvement: A summary of the 3rd International Conference on Malaysian Chinese Literature - Fan, P.W.; Hui, S.; Ling, T.S. (Central China Normal Univ, 2010)
Malaysian Chinese Literature has become a significant part of Malaysian Chinese culture. The Chinese language writers feel responsible for maintaining the ethnic consciousness and recording the history of Chinese pioneers in the region. Finding themselves between the identities of their original and new nations, the Malaysian Chinese authors are vacillating between sinicization and nativization. The conference, whose theme was set as ``Homeland Consciousness and Literary Evolvement'', was attended by foreign and local scholars. They treated Malaysian Chinese literature as part of world literature and emphasized both its uniqueness and multicultural content, reassessing its global standing. This will contribute to the internationalization of Malaysian Chinese Literature and its further study abroad, as well as to the rise in quality of criticism of Malaysian Chinese Literature.